Amphibology, Rhetoric and Hermeneutics in world of law (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The amphibology, such as presupposition, and two ways of solution: the rhetoricand hermeneutics. Hermeneutic ontology breaks off two sets of insights. These areuseful to strength legal worldview by interacting with the world of law such asPhilosophy of Law and power of word.
Keywords: Amphibology; Rhetoric; Hermeneutics; Law.